PERILAKU ANAK PANTI ASUHAN DI PANTI ASUHAN AS-SHOHWAH KELUARAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU - Nila Kesuma; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The As-Shohwah orphanage is a social welfare enterprise for orphans, orphans, orphans and the poor. As the social welfare institutions of As-Shohwah orphanage have a purpose to keep and save children to avoid ignorance. this study aims to determine the behavior of violations of regulations violated by As-shohwah orphanage children, and how socialization and social supervision in the orphanage. The population of 34 authors did not take samples because all the populations were sampel. This research uses quantitative descriptive research. Data collection techniques to determine the behavior of violations of regulations and socialization and social supervision is using a questionnaire. From the results of the study, the behavior of violation of the rules in the As-Shohwah orphanage is in the medium category (53.20%), because of the 11 indicators on the behavior of violations of the regulations there are some indicators that are still violated. Socialization and social monitoring at As-Shohwah orphanage consist of 14 indicators included in good category (78%).Keywords: Violation Behavior, Socialization, As-Shohwah Orphanage, Tampan,Pekanbaru